Bibliodrama: Introducing Stories from Narrative Traditions in the Development of Young People's Life Orientation - Jean Agten (MDPI AG, 2019)
Young people, in the age of puberty and early adolescence, are in need of images and narratives as role models to mirror their actual thoughts and feelings, and to stimulate the development of their (tradition(s)-related) life orientation. The development of a life orientation we see as a religiously or secularly founded process of identity construction—a work-in-progress; a process of ‘learning by doing’. This is described in Part I of this contribution. As Jacob Moreno, the founder of psychodrama stated: ‘Thinking is in the action’. ‘Doing’—being actively involved in a situation—is the defining characteristic of key persons and key objects in narratives. This is in line with John Dewey’s view that the activity new perspectives are created; learning by doing. In bibliodrama, making use of psychodrama techniques, connections are established between narratives from traditional (religious or secular) worldviews—but also from myths and fairy tales—and young people’s individual life experiences. Seemingly without effort and as child’s play, bibliodrama creates an encounter between the here-and-now and the once-and-then of narratives of long ago. The theoretical framework of this practice and the methods of bibliodrama are described in Part II. In Part III we present an example of bibliodrama performed with 18−20-year-old students of the Odisee Hogeschool (Odisee University of Applied Sciences) of Brussels (Belgium). We conclude our contribution with a few preliminary conclusions, a discussion and recommendations for the practice of bibliodrama in education to familiarise students with (religious and secular) life orientations traditions, in order to facilitate the construction of their own authentic life orientation.